Financial behaviour of young adults: the influence of socioeconomic status, financial literacy and parental financial socialization / Muhammad Amirual Azlam ... [et al.]. - Azlam, Muhammad Amirual; Abd Malek, Alia Nadhirah; Abdul Mutaliff, Faqihah Syazwani; Ghazali, Nurdia Azlin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This study aimed to analyze the factor influencing financial behavior among young working adults at Universiti Teknologi Mara (UiTM) Shah Alam, Selangor. The purpose was to determine whether these young adults exhibit good financial behavior and to identify which factors; socioeconomic status (academic qualification, income, number of dependents), financial literacy and parental financial socializations significantly impact their financial behavior. The sample comprised 210 respondents including employees of the institution. Data was collected through a self-administrated online questionnaire. The dependent variable, financial behavior was categorized into three levels: low, moderate and high. Descriptive statistics and Ordinal Logistic Regression were employed to assess the factors affecting financial behavior. The finding indicates that most young working adults do practice good financial behavior. Additionally, the results reveal that academic qualification, income and number of dependents do not significantly influence financial behavior. In contrast, financial literacy and parental financial socialization were identified as significant factors of financial behavior among young working adults.